Multi-component composite hydrogel as well as preparation method and application thereof
Through the use of multi-component composite hydrogel, the problems of breathability and hemostasis of traditional dressings in skin wound healing are solved, and the rapid and stable wound healing is achieved, with excellent antioxidant and antibacterial effects.
Patent Information
- Application Number
- CN202411649521.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing traditional dressings lack hemostatic ability, poor breathability when treating skin wounds, and are prone to adhere to the wound, resulting in secondary damage to the wound and affecting healing.
Using a multi-component composite hydrogel, including carboxymethyl yeast β-1,3-glucan, oxidized carboxymethyl cellulose and carboxymethyl chitosan, a three-dimensional network structure is formed by cross-linking of Schiff base. It has pro-angiogenesis, antioxidant and anti-inflammatory effects, improves wound healing ability, and has self-healing and injectable properties.
The hydrogel provides a suitable wet environment, promotes wound healing, improves healing speed and mechanical properties, has excellent antioxidant ability and antibacterial activity, and is suitable for filling and repairing irregular wounds.
Smart Images

Figure CN119161601A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of biomaterials, in particular to a multi-component composite hydrogel, a preparation method and application thereof. Background Art
[0002] The skin is the largest organ in the human body and is easily damaged by the external environment. Although it has a high potential for self-regeneration, severe skin defects heal slowly or do not heal spontaneously, which requires covering with skin substitutes. Currently, the most widely used dressings in clinical practice are traditional dressings such as gauze, cotton balls, bandages, etc. These traditional dressings have certain hygroscopic and protective effects on the treatment of general wounds. Although gauze is low in cost and has good absorption capacity for exudate and can keep wounds dry, these traditional dressings easily adhere to the wound, lack hemostatic ability, have poor air permeability, and can cause secondary damage to the wound surface, which is not conducive to the healing of specific wounds. Therefore, it is necessary to develop new medical dressings for treating skin wounds.
[0003] In recent years, hydrogels have shown great potential in wound repair. Hydrogels are three-dimensional network structures composed of physical or chemical cross-links of hydrophilic polymers. Due to their porous molecular structure, high water content, good biocompatibility, and biodegradability, hydrogels are candidates for use as dressings for various wounds. Summary of the Invention
[0004] The present invention provides a multi-component composite hydrogel, a preparation method and applications thereof, which has a simple preparation process, low cost, is environmentally friendly and pollution-free, and has greater potential in wound repair.
[0005] A multi-component composite hydrogel comprises carboxymethyl yeast beta-1,3-glucan, oxidized carboxymethyl cellulose and carboxymethyl chitosan.
[0006] The molecular weight of the carboxymethyl yeast beta-1,3-glucan is 400-600 kD.
[0007] The substitution degree of the carboxymethyl yeast β-1,3-glucan is 50%-60%, and within this range, the angiogenesis promoting activity is optimal.
[0008] The carboxylation degree of the carboxymethyl chitosan is ≥80%. When the carboxylation degree of the carboxymethyl chitosan is lower than 80%, the solubility of the raw material and the subsequent gelling performance are affected.
[0009] The mass ratio of the carboxymethyl yeast β-1,3-glucan, oxidized carboxymethyl cellulose, and carboxymethyl chitosan is 1:(1-3):(1-4). When the mass ratio exceeds this range, the gelation effect and gelation time of the multi-component composite hydrogel are affected.
[0010] When the multi-component composite hydrogel was stored at 25°C, a rheological test was performed within a stress range of 0.1 to 100%. When the angular frequency changed within the range of 0.1 to 100 rad / s, the storage modulus G' curve and the loss modulus G" curve intersected. Specifically, when the angular frequency changed from 0.1 to 4.6 rad / s, the loss modulus was less than the storage modulus, and when the angular frequency changed from 4.6 to 100 rad / s, the loss modulus was greater than the storage modulus.
[0011] The amine groups of the carboxymethyl chitosan react with the aldehyde groups of oxidized carboxymethyl cellulose to form a three-dimensional network hydrogel. The carboxyl groups of the carboxymethyl glucan and the amino groups of the carboxymethyl chitosan are attracted to each other through charge, forming ionic bonds. The carboxymethyl glucan adopts a three-dimensional helical conformation and is attached to the three-dimensional network hydrogel, which not only enhances the biological function of carboxymethyl yeast β-1,3-glucan but also improves its mechanical properties.
[0012] The multi-component composite hydrogel has a gelling time of 6 to 12 minutes. If the gelling time is too short, it will gel in the syringe and cannot be injectable; if the gelling time is too long, it will gel slowly at the wound and cannot adhere to the wound surface in time.
[0013] A method for preparing a multi-component composite hydrogel, comprising the following steps: (1) Preparation of carboxymethyl yeast β-1,3-glucan; (2) Preparation of oxidized carboxymethyl cellulose; (3) After the oxidized carboxymethyl cellulose and carboxymethyl yeast β-1,3-glucan are mixed and dissolved, the carboxymethyl chitosan aqueous solution is added and mixed to obtain a multi-component composite hydrogel; or, After carboxymethyl chitosan and carboxymethyl yeast β-1,3-glucan are mixed and dissolved, an oxidized carboxymethyl cellulose aqueous solution is added and mixed to obtain a multi-component composite hydrogel.
[0014] The carboxymethyl chitosan and oxidized carboxymethyl cellulose cannot be mixed before the carboxymethyl yeast β-1,3-glucan is added, otherwise, the carboxymethyl chitosan and oxidized carboxymethyl cellulose will gel, resulting in the inability to mix the yeast β-1,3-glucan.
[0015] Specifically, the method for preparing the multi-component composite hydrogel includes: (1) Yeast β-1,3-glucan is added to isopropanol, followed by addition of sodium hydroxide aqueous solution, stirring for 0.5 to 1.5 hours, adding monochloroacetic acid aqueous solution dropwise, heating to 50 to 70°C after addition, stirring for 1 to 4 hours, separating the reaction solution, removing the lower layer, pouring it into methanol, stirring for 0.5 to 1 hour, precipitating, and drying to obtain carboxymethyl yeast β-1,3-glucan sodium salt, dissolving the obtained carboxymethyl yeast β-1,3-glucan sodium salt in water, adding hydrochloric acid aqueous solution after dissolution to adjust the pH to 2 to 3, pouring it into a mixed solvent, stirring for 10 to 30 minutes, filtering, washing with ethanol, and drying to obtain carboxymethyl yeast β-1,3-glucan; (2) Add carboxymethyl cellulose to sodium periodate solution, stir at 20-40°C for 4-10 hours, filter, and dry to obtain a crude product. Add the crude product to ethylene glycol aqueous solution, stir for 10-30 minutes, filter, wash with deionized water, and dry to obtain oxidized carboxymethyl cellulose; (3) adding oxidized carboxymethyl cellulose to deionized water, adding carboxymethyl yeast β-1,3-glucan, dissolving it, adding carboxymethyl chitosan aqueous solution, mixing, and standing for 10 to 30 minutes to obtain a multi-component composite hydrogel; or, Carboxymethyl chitosan was added into deionized water, carboxymethyl yeast β-1,3-glucan was added and dissolved, and an aqueous solution of oxidized carboxymethyl cellulose was added, mixed, and allowed to stand for 10 to 30 minutes to obtain a multi-component composite hydrogel.
[0016] In step (1), the mass ratio of the yeast β-1,3-glucan, isopropyl alcohol, sodium hydroxide aqueous solution, and monochloroacetic acid aqueous solution is 1: (20-60): (0.3-0.8): (0.2-1).
[0017] Wherein, the concentration of the sodium hydroxide aqueous solution is 13-15 mol / L; The concentration of the monochloroacetic acid aqueous solution is 1-3 mol / L; The concentration of the hydrochloric acid aqueous solution is 1-3 mol / L.
[0018] The mixed solvent is a mixed solution of isopropyl alcohol and ethanol, and the mass ratio of the isopropyl alcohol to the ethanol is (2~1):1.
[0019] In step (2), the mass ratio of the carboxymethyl cellulose to the sodium periodate solution is 1:(4-20).
[0020] The sodium periodate solution is an aqueous solution of sodium periodate, wherein the mass ratio of sodium periodate to water is 1:(13-18).
[0021] In step (3), the mass ratio of the carboxymethyl yeast β-1,3-glucan to deionized water is 1:(15-30).
[0022] The mass concentration of the carboxymethyl chitosan aqueous solution is 4-6wt%; The mass concentration of the oxidized carboxymethyl cellulose aqueous solution is 4-6 wt %.
[0023] The present invention also provides the use of the multi-component composite hydrogel in wound dressings or wound repair materials.
[0024] The multi-component composite hydrogel has a DPPH free radical scavenging rate of not less than 40%, and has excellent antioxidant capacity.
[0025] A wound dressing is characterized by using a multi-component composite hydrogel of carboxymethyl yeast β-1,3-glucan as an active ingredient.
[0026] A wound repair material is characterized by using a multi-component composite hydrogel of carboxymethyl yeast β-1,3-glucan as an active ingredient.
[0027] Preferably, the wound dressing or wound repair material further comprises necessary auxiliary materials, including a supporting material, an absorbing layer, and a protective film.
[0028] Yeast β-1,3-glucan consists of β-(1→3)-linked linear chains and numerous β-(1→6)-linked branched structures. Due to its highly branched structure, it adopts a three-dimensional helical conformation. This unique structure endows yeast β-1,3-glucan with multiple biological functions, including immunomodulatory, anti-inflammatory, and antioxidant properties, all of which have positive effects on wound repair. However, the complex and highly branched structure of yeast β-1,3-glucan results in poor water solubility, limiting its application in wound healing. Carboxymethylation is an effective method for structural modification of yeast β-1,3-glucan. The introduction of carboxymethyl groups significantly improves its water solubility and bioactivity.
[0029] Beneficial effects: 1. The present invention prepares a multi-component composite hydrogel by mixing carboxymethyl yeast β-1,3-glucan, oxidized carboxymethyl cellulose, and carboxymethyl chitosan. Carboxymethyl yeast β-1,3-glucan has angiogenic, immunomodulatory, and antioxidant effects. Oxidized carboxymethyl cellulose and carboxymethyl chitosan are cross-linked via Schiff base to form a gel, resulting in a three-dimensional network hydrogel structure. This hydrogel not only exhibits excellent air permeability and water retention, providing a suitable moist environment for wound healing and promoting wound healing, but also exhibits self-healing and injectability, enabling the multi-component composite hydrogel to regenerate in situ and fill irregular wound areas. Furthermore, the carboxymethyl chitosan exhibits antibacterial activity, promoting wound healing.
[0030] 2. The present invention uses carboxymethyl yeast β-1,3-glucan as raw material. Its spiral structure not only improves the wound healing ability of the multi-component composite hydrogel, but also cooperates with the three-dimensional network structure of the hydrogel to improve the mechanical properties of the multi-component composite hydrogel, enabling it to deform when subjected to force and adapt to surfaces of different shapes, thereby improving its adhesion. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of the multi-component composite hydrogel prepared in Example 1; Figure 2 This is a self-healing image of the multi-component composite hydrogel prepared in Example 1; Figure 3 This is an image of the injectable properties of the multi-component composite hydrogel prepared in Example 1; Figure 4 This is a frequency scan diagram of the multi-component composite hydrogel prepared in Example 1; Figure 5 This is a strain scan diagram of the multi-component composite hydrogel prepared in Example 1; Figure 6 This is a continuous strain alternating scanning diagram of the multi-component composite hydrogel prepared in Example 1; Figure 7 This is an image of red blood cells treated with the multi-component composite hydrogel prepared in Example 1 in the hemolysis test; Figure 8 DPPH free radical scavenging activity after treatment with the multi-component composite hydrogel prepared in Example 1; Figure 9 The statistical results of L929 cell activity evaluation after incubation with the multi-component composite hydrogel extract prepared in Example 1 for 24 h, 48 h, and 72 h; Figure 10 These are the migration images of L929 cells after incubation with the multi-component composite hydrogel extract prepared in Example 1 for 12 h, 24 h, and 48 h; Figure 11 The live / dead images of cells after incubation with the multi-component composite hydrogel extract prepared in Example 1 for 24 h, 48 h, and 72 h; Figure 12 The multi-component composite hydrogel prepared in Example 1 promoted wound healing in diabetic mice. DETAILED DESCRIPTION
[0032] The technical solution of the present invention is further illustrated by the following examples. In the following implementation process, unless otherwise specified, the raw materials are all commercially available. Yeast β-1,3-glucan was purchased from Sigma-Aldrich, product number G5011.
[0033] Example 1: The carboxymethyl yeast β-1,3-glucan used in this example has a molecular weight of 500 kD and a degree of substitution of 55.1%. The degree of carboxylation of carboxymethyl chitosan is greater than 80%.
[0034] A multi-component composite hydrogel, prepared by: (1) Preparation of carboxymethyl yeast β-1,3-glucan: 3 kg of yeast β-1,3-glucan was added to 60 kg of isopropanol, 1.2 kg of 14.3 mol / L sodium hydroxide aqueous solution was slowly added, and the mixture was stirred for alkalization for 1 hour. 2.5 kg of 2.1 mol / L monochloroacetic acid aqueous solution was added dropwise, and the temperature was raised to 60 ° C. After stirring for 2 hours, the reaction solution was separated into layers, the lower layer was removed, and poured into 300 kg of methanol, stirred for 45 minutes, and the solid was precipitated and dried to obtain carboxymethyl yeast β-1,3-glucan sodium salt. The obtained carboxymethyl yeast β-1,3-glucan sodium salt was dissolved in 30 kg of water, and 2 mol / mL of hydrochloric acid aqueous solution was added to adjust the pH to 2.5. The mixture was poured into a mixed solution of 200 kg of isopropanol and ethanol (the mass ratio of isopropanol to ethanol was 2:1), stirred for 30 minutes, filtered, and the solid was washed with 100 kg of ethanol and dried to obtain carboxymethyl yeast β-1,3-glucan; (2) 6 kg of carboxymethyl cellulose was placed in a brown conical flask, sodium periodate solution was added, stirred at 30 °C for 8 hours, filtered, and dried to obtain a white block crude product. The crude product was added to 30 kg of ethylene glycol aqueous solution (0.1 mol / mL), stirred for 20 minutes, filtered, and the solid was washed with 100 kg of deionized water and dried to obtain oxidized carboxymethyl cellulose; (3) 1.5 kg of oxidized carboxymethyl cellulose obtained in step (2) was added to 30 kg of deionized water, and 1.5 kg of carboxymethyl yeast β-1,3-glucan obtained in step (1) was added and dissolved by ultrasonication. 40 kg of a 5% by mass carboxymethyl chitosan aqueous solution was added, mixed, and allowed to stand for 20 minutes to obtain a multi-component composite hydrogel.
[0035] The sodium periodate solution was prepared as follows: 6.4 kg of sodium periodate was dissolved in 100 kg of deionized water to obtain a sodium periodate solution.
[0036] Example 2: This embodiment is the same as embodiment 1, except that step (3) is: 1.5 kg of carboxymethyl chitosan was added to 30 kg of deionized water, and 1.5 kg of carboxymethyl yeast β-1,3-glucan obtained in step (1) was added and dissolved by ultrasonication. 40 kg of 5% by mass oxidized carboxymethyl cellulose aqueous solution was added, mixed, and allowed to stand for 20 minutes to obtain a multi-component composite hydrogel.
[0037] Comparative Example 1: This comparative example is the same as Example 1, except that the mass ratio of the carboxymethyl yeast β-1,3-glucan, oxidized carboxymethyl cellulose, and carboxymethyl chitosan is 1:3:0.5.
[0038] Comparative Example 2: This comparative example is the same as Example 1, except that carboxymethyl yeast β-1,3-glucan is not added in this comparative example.
[0039] Test example: (1) Gelation time test The inversion-no-backflow observation method was used. 2 mL of each of the hydrogels prepared in Examples 1-2 and Comparative Example 1 was placed in a glass bottle with a rubber stopper. The time was counted from the start of pouring, and observation was made every 1 minute until no backflow occurred upon inversion. The results are shown in Table 1.
[0040] Table 1 Gelation time test results
[0041] It can be seen from the results in Table 1 that the multi-component composite hydrogels prepared in Example 1 and Example 2 have a relatively fast gelation time, which is conducive to rapid gelation at the wound, acting as a protective barrier and helping the wound to heal.
[0042] (2) Micromorphological characteristics The freeze-dried multi-component composite hydrogel was subjected to gold spraying treatment, and the microscopic morphology of the multi-component composite hydrogel prepared in Example 1 was observed using a scanning electron microscope (Quattro S). Figure 1 As shown. Figure 1 It can be seen from the results that the multi-component composite hydrogel presents a three-dimensional porous morphology with relatively uniform distribution.
[0043] (3) Self-healing characteristics test Self-healing ability is important for hydrogel dressings because it can fill the wound area and withstand external mechanical forces and extend the service life of the hydrogel. The self-healing performance of the multi-component composite hydrogel prepared in Example 1 was evaluated by direct visual method. Two pieces of red and blue multi-component composite hydrogels were placed together at room temperature without any external intervention and their self-healing behavior was observed within 1 hour. The results are shown in Figure 2. Figure 2 As shown, the two multi-component composite hydrogels can reform into a complete cylindrical hydrogel in the absence of external force, proving that the multi-component composite hydrogel prepared in Example 1 has good self-healing properties.
[0044] (4) Injectability test Continuously squeeze out the letters "XCH" through a 5mL syringe. The result is as follows Figure 3 As shown, the injectability and wound shape adaptability of the multi-component composite hydrogel prepared in Example 1 were confirmed.
[0045] (5) Rheological properties test The hydrogel was placed on a rheometer, set at 37°C and a strain of 1%. The multi-component composite hydrogel prepared in Example 1 was subjected to a frequency sweep, with different angular frequencies of 0.1-100 rad / s applied. The storage modulus (G′) and loss modulus (G″) were analyzed. The results are shown in Figure 2. Figure 4 shown. Figure 4 It can be seen from the results that the storage modulus (G′) of the multi-component composite hydrogel prepared in Example 1 exceeds the loss modulus (G″), which means that the multi-component composite hydrogel has gel-state behavior.
[0046] The temperature was set at 25°C, and amplitude sweep was performed. By changing the stress range γ = 0.1-100%, the critical strain point of the multi-component composite hydrogel was detected, and the changes of G′ and G″ of the multi-component composite hydrogel with strain were investigated. The results are shown in Figure 2. Figure 5 shown. Figure 5 The results show that the intersection between G′ and G″ of the multi-component composite hydrogel is 4.6%, indicating that the network of the multi-component composite hydrogel obtained in Example 1 is destroyed.
[0047] The temperature was set at 25°C and the frequency was 1 Hz. The strain was alternately scanned. First, the strain was set to 1% and the time scan test was performed for 60 seconds. Then, the strain was set to 800% and the time scan was performed for 25 seconds. The test was repeated for 5 cycles to investigate the changes in G′ and G″ of the multi-component composite hydrogel prepared in Example 1. The results are shown in FIG. Figure 6 shown. Figure 6 The results show that after five rheological cycles, G′ and G″ also returned to their original values, proving that the multi-component composite hydrogel has good self-healing ability and a relatively stable structure. When the strain is 800%, the decrease in G′ indicates that the multi-component composite hydrogel network obtained in Example 1 is destroyed.
[0048] (6) In vitro hemolysis test 1 mL of rabbit anticoagulated whole blood was slowly added to 10 mL of PBS. The blood was evenly dispersed with a pipette to suspend the red blood cells. The blood was centrifuged at 1000 rpm for 7 min. The supernatant was slowly aspirated and discarded. 10 mL of PBS was added and the centrifugation was repeated three times until the supernatant was colorless and transparent. The red blood cells precipitated in the last step were collected and recorded as 100 wt%. A red blood cell diluent with a concentration of 4 wt% was prepared with PBS for later use.
[0049] The multi-component composite hydrogel prepared in Example 1 was added to deionized water to prepare 500 μg / mL, 1 mg / mL, 1.5 mg / mL, and 2 mg / mL multi-component composite hydrogel suspensions. 500 μL of 4 wt% red blood cell dilution was added to each suspension, and the suspension was incubated in a 37°C constant temperature water bath for 1 hour. The suspension was taken out and centrifuged at 1000 r / min for 10 minutes to serve as the sample group. PBS was used as a blank group, and Triton X-100 with a mass concentration of 1% was used as a control group. The results are shown in FIG. Figure 7 shown.
[0050] Figure 7 The results show that the supernatants of the multi-component composite hydrogels with concentrations of 500 μg / mL, 1 mg / mL, 1.5 mg / mL, and 2 mg / mL are almost completely transparent, indicating that the multi-component composite hydrogel prepared in Example 1 has a low hemolysis rate. The supernatant was taken in a 96-well plate and the absorbance measured at 540 nm using a microplate reader was less than 5%, further demonstrating that the multi-component composite hydrogel prepared in Example 1 has a low hemolysis rate.
[0051] (7) DPPH free radical scavenging experiment The antioxidant properties of the multi-component composite hydrogel were determined by DPPH free radical scavenging experiment. The specific steps are as follows: a. The multi-component composite hydrogel prepared in Example 1 after freeze-drying was dissolved in 75 wt% methanol. Methanol solutions of the multi-component composite hydrogel with concentrations of 500 μg / mL, 1 mg / mL, 1.5 mg / mL, and 2 mg / mL were prepared as sample groups. 1 mL of the sample group solution was added to 1 mL of DPPH methanol solution (0.2 mM). The mixture was incubated in the dark for 30 min, and the absorbance A was measured at 517 nm. 样 .
[0052] b. Take a mixture of 1 mL of methanol solution containing multi-component composite hydrogel and 1 mL of 75 wt% methanol as a blank group and measure the absorbance A according to the method in step a. 空 .
[0053] c. Use a mixture of 1 mL of DPPH methanol solution (0.2 mM) and 1 mL of 75 wt% methanol solution as the control group and measure the absorbance A according to the method in step a. 对 .
[0054] d. Calculate the DPPH clearance rate according to the following formula: .
[0055] The results are as follows Figure 8 As shown, Figure 8The results show that the multi-component composite hydrogel prepared in Example 1 has a good DPPH scavenging effect, which proves that it has good antioxidant properties.
[0056] (8) Cytotoxicity test a. L929 cells were cultured in MEM medium containing fetal bovine serum and double-antibody. L929 cells were seeded into a 96-well plate at a cell density of 5000 cells / well. After the cells adhered, the culture medium was removed and the sample group extract was added. The cells were cultured for 24 h, 48 h, and 72 h, respectively. CCK-8 was added and the cells were incubated for 1 h. The absorbance OD1 was measured at 450 nm using a microplate reader.
[0057] Preparation of the sample group extracts: 100 mg of the multi-component composite hydrogel obtained in Example 1 was weighed and added to a centrifuge tube. 10 ml of MEM was added and incubated at 37°C for 24 hours. The mixture was centrifuged and filtered through a microporous filter membrane to obtain multi-component composite hydrogel extracts with concentrations of 50 μg / mL, 200 μg / mL, and 800 μg / mL.
[0058] b. Use a cell-free control group as the blank control group, and measure the absorbance OD0 according to the method in step a; use cells incubated with no hydrogel as the cell control group, and measure the absorbance OD2 according to the method in step a.
[0059] c. Calculate cell viability using the following formula: .
[0060] Among them, OD1 is the absorbance value of the sample group, OD2 is the absorbance value of the cell control group, and OD0 is the absorbance value of the blank control group. The calculation results are as follows Figure 9 As shown, the blank group is the cell viability of the cell control group. Figure 9 The results show that after L929 cells were incubated with the MEM culture medium containing the multi-component composite hydrogel prepared in Example 1, the cell survival rate was very high, proving that the multi-component composite hydrogel prepared in Example 1 was non-toxic to L929 cells.
[0061] (9) Cell scratch test L929 cells were seeded in a 6-well plate at a cell density of 500,000 cells / well and cultured in MEM medium containing fetal bovine serum and double-antibody. After the cells adhered, three lines were drawn in each well with a 200 μL pipette tip. The extracts of the multi-component composite hydrogel prepared in Example 1 were added at concentrations of 50 μg / mL, 200 μg / mL, and 800 μg / mL, respectively. The cells were incubated for 12 h, 24 h, and 48 h, and photographed under a microscope. The results are shown in FIG. Figure 10 As shown, the blank group did not add the multi-component composite hydrogel extract. Figure 10 The results show that as the concentration of the multi-component composite hydrogel prepared in Example 1 increases, the migration ability of L929 cells becomes stronger, and the scratches in the high-concentration group are basically closed, which confirms that the multi-component composite hydrogel prepared in Example 1 is beneficial to the migration of fibroblasts in the wound as a wound dressing.
[0062] (10) Cell live / dead staining test L929 cells were seeded in a 96-well plate at a cell density of 5000 cells / well. After the cells adhered, the culture medium was removed and the extracts of the multi-component composite hydrogel prepared in Example 1 were added at concentrations of 50 μg / mL, 200 μg / mL, and 800 μg / mL, respectively. The cells were incubated for 24 h, 48 h, and 72 h, respectively. The live / dead cells were fluorescently stained using a Calcein AM / PI cell activity detection kit. The cells were incubated at 37°C in the dark for 30 min and photographed using a fluorescence inverted microscope. The live cells were stained with Calcein AM reagent and the dead cells were stained with PI reagent. The results are shown in FIG. Figure 11 As shown. Figure 11 The results show that after L929 cells were incubated with the MEM culture medium containing the multi-component composite hydrogel prepared in Example 1, the cell survival rate was very high and the number of dead cells was small. As the incubation time increased, the cell proliferation increased.
[0063] (11) Promote wound healing in diabetic mice Six-week-old C57BL / 6J male mice (weighing about 25g) were fasted for 4 hours and intraperitoneally injected with streptozotocin at a dose of 5mg / 100g for 5 consecutive days. One week after the injection, the fasting blood glucose levels of the mice were measured, and 18 mice with blood glucose levels greater than 16.6mmol / L were randomly divided into a model group, a two-component drug group, and a three-component drug group, with 6 mice in each group. All mice were anesthetized with chloral hydrate, the hair on the back of the mice was shaved off, and a wound with a diameter of about 1 cm was made on the back with a punch. The wounds in the model group were not treated in any way, and the two-component drug group and the three-component drug group were covered with the hydrogels prepared in Example 2 and Example 1 with a diameter of 1 cm and a thickness of 3 mm, respectively. All mice were photographed on the 0th, 6th, and 18th days of breeding to observe the healing of the back wounds. The results are as follows Figure 12 As shown, after the mouse wound was treated with the multi-component composite hydrogel prepared in Example 1, the healing speed was significantly accelerated. On the 18th day, the wound was almost completely healed, proving that the multi-component composite hydrogel prepared in the present invention can significantly promote the healing of the wound surface of diabetic mice.
Claims
1. A multi-component composite hydrogel, characterized in that: Including carboxymethyl yeast β-1,3-glucan, oxidized carboxymethyl cellulose, carboxymethyl chitosan; The degree of substitution of the carboxymethyl yeast β-1,3-glucan is 50%-60%; The molecular weight of the carboxymethyl yeast β-1,3-glucan is 400-600 kD.
2. The multi-component composite hydrogel according to claim 1, characterized in that: The mass ratio of the carboxymethyl yeast β-1,3-glucan, oxidized carboxymethyl cellulose and carboxymethyl chitosan is 1:(1-3):(1-4).
3. The multi-component composite hydrogel according to claim 1, characterized in that: The carboxylation degree of the carboxymethyl chitosan is ≥80%.
4. The multi-component composite hydrogel according to claim 1, characterized in that: The gelling time of the multi-component composite hydrogel is 6 to 12 minutes.
5. A method for preparing a multi-component composite hydrogel according to claim 1, characterized in that the steps include: (1) Preparation of carboxymethyl yeast β-1,3-glucan; (2) Preparation of oxidized carboxymethyl cellulose; (3) After the oxidized carboxymethyl cellulose and carboxymethyl yeast β-1,3-glucan are mixed and dissolved, the carboxymethyl chitosan aqueous solution is added and mixed to obtain a multi-component composite hydrogel; or, After carboxymethyl chitosan and carboxymethyl yeast β-1,3-glucan are mixed and dissolved, an oxidized carboxymethyl cellulose aqueous solution is added and mixed to obtain a multi-component composite hydrogel.
6. The method for preparing a multi-component composite hydrogel according to claim 5, characterized in that the steps include: (1) Yeast β-1,3-glucan is added to isopropanol, and then sodium hydroxide aqueous solution is added, stirred for alkalization for 0.5 to 1.5 hours, monochloroacetic acid aqueous solution is added dropwise, and the temperature is raised to 50 to 70°C after the addition is completed. The reaction solution is stirred for 1 to 4 hours to separate into layers, and the lower layer is taken out and poured into methanol, stirred for 0.5 to 1 hour, precipitated, and dried to obtain carboxymethyl yeast β-1,3-glucan sodium salt. The obtained carboxymethyl yeast β-1,3-glucan sodium salt is dissolved in water, and after dissolution, hydrochloric acid aqueous solution is added to adjust the pH to 2 to 3, and then poured into a mixed solvent, stirred for 10 to 30 minutes, filtered, washed with ethanol, and dried to obtain carboxymethyl yeast β-1,3-glucan; (2) adding carboxymethyl cellulose to a sodium periodate solution, stirring at 20-40° C. for 4-10 hours, filtering, and drying to obtain a crude product, adding the crude product to an ethylene glycol aqueous solution, stirring for 10-30 minutes, filtering, washing with deionized water, and drying to obtain oxidized carboxymethyl cellulose; (3) adding oxidized carboxymethyl cellulose to deionized water, adding carboxymethyl yeast β-1,3-glucan, dissolving, adding carboxymethyl chitosan aqueous solution, mixing, and standing for 10 to 30 minutes to obtain a multi-component composite hydrogel; or, Carboxymethyl chitosan was added into deionized water, carboxymethyl yeast β-1,3-glucan was added and dissolved, and oxidized carboxymethyl cellulose aqueous solution was added, mixed, and allowed to stand for 10 to 30 minutes to obtain a multi-component composite hydrogel.
7. The method for preparing a multi-component composite hydrogel according to claim 6, characterized in that the steps include: In step (1), the mixed solvent is a mixed solution of isopropanol and ethanol; In step (2), the sodium periodate solution is an aqueous solution of sodium periodate.
8. Use of the multi-component composite hydrogel of carboxymethyl yeast β-1,3-glucan as claimed in any one of claims 1 to 4 or the multi-component composite hydrogel of carboxymethyl yeast β-1,3-glucan prepared by the preparation method of any one of claims 5 to 7 in wound dressings or wound repair materials.
9. The application according to claim 8, characterized in that: The multi-component composite hydrogel has a DPPH free radical scavenging rate of not less than 40%.
Citation Information
Patent Citations
Method for preparing carboxymethyl yeast glucan product and product obtained by using same
CN103804511A
Multi-component hydrogel containing fragrant snail bioactive peptide as well as preparation method and application of multi-component hydrogel
CN118924677A
Injectable hydrogel material and preparation method therefor and use thereof
WO2021007899A1
